2015
DOI: 10.3109/01942638.2015.1012319
|View full text |Cite
|
Sign up to set email alerts
|

Attention in 3-Year-Old Children with VLBW and Relationships with Early School Outcomes

Abstract: At preschool age, children with VLBW have attention difficulties. Attentive behavior at preschool age is a predictor of school career 2 years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They found that parents of extremely low birth weight children rated them more highly (indicating more problem behaviours with inhibition) than did parents of children with normal birth weight. Verkerk et al (2016) also reported differences at 3 years in very low birth weight compared to normal birth weight children on the BRIEF-P. Parents and teachers of preterm children rated them as having more problem behaviours on the child version of the same scale at 4-5 years (O'Meagher et al, 2019) and at 8 years (Anderson et al, 2011). As did parents of 17-year-old adolescents who were extremely preterm or extremely low birth weight at birth (Wilson-Ching et al, 2013).…”
Section: Parent Reportmentioning
confidence: 92%
See 1 more Smart Citation
“…They found that parents of extremely low birth weight children rated them more highly (indicating more problem behaviours with inhibition) than did parents of children with normal birth weight. Verkerk et al (2016) also reported differences at 3 years in very low birth weight compared to normal birth weight children on the BRIEF-P. Parents and teachers of preterm children rated them as having more problem behaviours on the child version of the same scale at 4-5 years (O'Meagher et al, 2019) and at 8 years (Anderson et al, 2011). As did parents of 17-year-old adolescents who were extremely preterm or extremely low birth weight at birth (Wilson-Ching et al, 2013).…”
Section: Parent Reportmentioning
confidence: 92%
“…Five studies were found which used parent report measures of executive attention (Anderson et al, 2011;Baron et al, 2011;O'Meagher et al, 2019;Verkerk et al, 2016;Wilson-Ching et al, 2013). Impairments were consistently reported for the preterm groups (Table 4).…”
Section: Parent Reportmentioning
confidence: 99%
“…Verkerk et al have provided further evidence of attention difficulties amongst VLBW children at preschool age and have identified that these difficulties predict school performance 2 years later (Verkerk et al, 2016). Van de Weijer-Bergsma et al proposed that both biological and environmental factors influence the development of attention in later years.…”
Section: Impact Of Preterm Birth On Attention In Early Childhoodmentioning
confidence: 99%